Studies on a Factor in Sweet Potato Root Which Agglutinates Spores of Ceratocystis fimbriata, Black Rot Fungus - Kojime, Mineo (1982)
A factor which agglutinated the spores of Ceratocystis fimbriata in the presence of Ca(2+) was purified from sweet potato (Ipomea batatas Lam cv. Norin[1]) root. Element composition of the purified factor was as follows; analysis found: C (29.8%), H (3.97%), O (65.34%), N (0.81%): calculated for C(43)H(69)O(70)N(1): C (30.02%), H (4.01%), O (65.15%), N (0.81%). The factor was mainly composed of galacturonic acid (53% of dry weight) and contained arabinose, fucose, and unidentified component as minor components. The factor also agglutinated A-, B-, AB-, and O types of human erythrocytes to almost the same degree in the presence of Ca(2+). The differential spore-agglutinating activity of the factor depended on the pH of the assay medium; it agglutinated similarly the germinated spores of sweet potato and coffee strains at pH 7.5 and 5.5, whereas it displayed a distinct differential agglutinating activity at pH 6.5. The factor was assayed for spore-agglutinating activity at pH 6.5, using the germinated and ungerminated spores of seven strains of C. fimbriata; sweet potato, coffee, prune, cacao, oak, taro, and almond strains. The factor agglutinated ungerminated spores of all seven strains similarly, although small differences were observed among strains. On the other hand, a clear differential agglutination was observed among the germinated spores of various strains; sweet potato and almond strains were highly insensitive in comparison with other strains. The growth of the agglutinated spores of C. fimbriata was inhibited. These results are discussed in relation to host-parasite specificity.